Inovasi, tantangan, serta penyesuaian Perpustakaan Daerah Kabupaten Subang di masa pandemi Covid-19 - Annisa Fitriana Putri Rieswansyah; Sukaesih Sukaesih; Evi Nursanti Rukmana; Asep Saeful Rohman (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The condition of the Covid-19 pandemic, which has not ended yet, continues to demand that everyone innovate so that they can carry out their activities as before by prioritizing health. All types of activities in society are hampered, such as the economic, education, government, and even public services sectors, including information institutions or library institutions. This research and scientific writing aims to explain how libraries can continue to adapt even in the midst of a pandemic by producing a new form of service or innovation in library services to continue providing services to the community and explaining what challenges or obstacles are experienced during the adjustment period at the Archive Office and Subang Regency Regional Library. This research was conducted using descriptive qualitative methods with the process of collecting data through field observations. Interviews, and literature study. The results showed that the innovation carried out was by developing services in digital form and still operating with limited visitors by quarantining books that were used by users. In these development activities, the main challenges were encountered, namely the low reading interest of the community, limited development budgets, and the availability of competent human resources. In conclusion, innovation is the key for the Regency Archives and Library Service in improving services amid the Covid-19 pandemic.